The use of antimuscarinics, phosphodiesterase type V inhibitors and phytotherapy for lower urinary tract symptoms in men - Kok Kit Ng; Foo Cheong Ng (Asian Journal of Urology)
Besides the mainstay of α-blockers and 5α-reductase inhibitors, other forms of medical therapy complete the armamentarium in the treatment of lower urinary tract symptoms (LUTS) in men. These treatments can target specific symptoms as well as associated symptoms that would affect the quality of life of the patients. Many patients are bothered by storage symptoms, more so than the voiding symptoms. Antimuscarinics are efficacious and safe, provided the patients do not have high post void residual urine. Many patients with LUTS also have erectile dysfunction, and phosphodiesterase type V inhibitors are effective in relieving both LUTS as well as erectile dysfunction for such patients. Phytotherapy provides a popular and safe treatment for LUTS, however, the efficacy of the treatment has not been proven in well conducted prospective randomized controlled studies. Keywords: Benign prostatic hyperplasia, Erectile dysfunction, Lower urinary tract symptoms, Muscarinic antagonists, Phosphodiesterase 5 inhibitors, Phytotherapy